Determinants of early lexical acquisition: Effects of word- and child-level factors on Dutch children's acquisition of words. Issue 6 (19th November 2022) - VERHAGEN, Josje; VAN STIPHOUT, Mees; BLOM, Elma
Abstract: Previous research on the effects of word-level factors on lexical acquisition has shown that frequency and concreteness are most important. Here, we investigate CDI data from 1, 030 Dutch children, collected with the short form of the Dutch CDI, to address (i) how word-level factors predict lexical acquisition, once child-level factors are controlled, (ii) whether effects of these word-level factors vary with word class and age, and (iii) whether any interactions with age are due to differences in receptive vocabulary. Mixed-effects regressions yielded effects of frequency and concreteness, but not of word class and phonological factors (e.g., word length, neighborhood density). The effect of frequency was stronger for nouns than predicates. The effects of frequency and concreteness decreased with age, and were not explained by differences in vocabulary knowledge. These findings extend earlier results to Dutch, and indicate that effects of age are not due to increases in vocabulary knowledge.